The Influence of Work Environment and Work Flexibility on Job Satisfaction with Competence as an Intervening Variable in BPJS Employment Pematang Siantar Branch and Kisaran Branch - Manullang, Lasber; B, Mesra (CV. Lafadz Jaya, 2024)
This research is useful for looking at the influence of work environment, flexibility on job satisfaction and competence. This research took as its object a BPJS Employment company office, Pematang Siantar and Kisaran Branches. The lack of work environment at BPJS Employment Pematang Siantar and Kisaran Branches can also affect work flexibility, because these two things have a close continuity. In fact, the conditions of the work environment around the research have several problems for the employees who work there. Employee discomfort at work will certainly affect employee flexibility so that the satisfaction of company officials will certainly have an influence. Even though the assessment of the work environment is again a personal assessment of each employee, in general, in fact, this actually has an influence on work flexibility and job satisfaction. Several things that happened at BPJS Employment Pematang Siantar and Kisaran Branches were the lack of communication between employees and even between employees and superiors, which was one of the reasons for the poor working environment conditions. This lack of communication between employees will cause new problems that will affect work flexibility and possibly even more employees' future. The results of this research are as follows: Work Flexibility has a positive and insignificant effect on Job Satisfaction with an original sample value of 0.161 and an ap value of 0.154. Work Flexibility has a positive and significant effect on Competency with an original sample value of 0.786 p value 0.000. Competency has a positive and significant effect on Job Satisfaction with an original sample value of 0.583 and ap value of 0.000. Work Environment has a positive and significant effect on Job Satisfaction with an original sample value of 0.193 and ap value of 0.016. Work Environment has a positive and significant effect on Competency with an original sample value of 0.165 and ap value of 0.016. Job Flexibility has a positive and significant indirect effect on Job Satisfaction through Job Satisfaction with a value of 0.457 and a value of 0.000. Work Environment has a positive and significant indirect effect on Job Satisfaction through competency with an original sample value of 0.096 and ap value of 0.000.